Analisis Yuridis Penggunaan Sertifikat Tanah Milik Orang Lain Sebagai Jaminan Utang Piutang - Saragih, Gracia Charlita; Tarina, Dwi Desi Yayi (Media Hukum Indonesia (MHI), 2024)
The use of land certificates owned by other people as collateral in debt transactions is a common practice in society, but it raises various legal issues. This study aims to analyze the legal validity, legal implications, and legal protection for the parties involved, especially land certificate owners who are not debtors. This study was conducted with a normative approach that refers to the provisions of the Civil Code, the Basic Agrarian Law, and other related regulations. The results of the analysis show that the use of land certificates owned by other people can be considered valid if it is based on a clear written agreement and explicit consent from the certificate owner. However, these practices are at risk of causing disputes if the agreement does not meet the requirements for a valid agreement in civil law or there is misuse of collateral by the debtor. In addition, legal protection for land certificate owners who are not directly involved in the transaction is still less than optimal, so it is necessary to strengthen regulations and administrative procedures to ensure legal certainty. This study recommends the need for stricter regulations regarding the use of land certificates as collateral, including the obligation to record agreements at the land office and an effective legal protection mechanism for land owners. Thus, it is hoped that this practice can be carried out safely and in accordance with applicable legal principles.